The first detections of the key prebiotic molecule PO in star-forming regions. Issue Volume 13:Issue S332(2017) (4th September 2018) - Rivilla, Víctor M.; Fontani, Francesco; Beltrán, Maite; Vasyunin, Anton; Caselli, Paola; Martín-Pintado, Jesús; Cesaroni, Riccardo
Abstract: Phosphorus is a crucial element in prebiotic chemistry, especially the P−O bond, which is key for the formation of the backbone of the deoxyribonucleic acid. So far, PO had only been detected towards the envelope of evolved stars, and never towards star-forming regions. We report the first detection of PO towards two massive star-forming regions, W51 e1/e2 and W3(OH), using data from the IRAM 30m telescope. PN has also been detected towards the two regions. The abundance ratio PO/PN is 1.8 and 3 for W51 and W3(OH), respectively. Our chemical model indicates that the two molecules are chemically related and are formed via gas-phase ion-molecule and neutral-neutral reactions during the cold collapse. The molecules freeze out onto grains at the end of the collapse and desorb during the warm-up phase once the temperature reaches ~35 K. The observed molecular abundances of 10 −10 are predicted by the model if a relatively high initial abundance of 5× 10 −9 of initial phosphorus is assumed.